Exploring the bacteriome of Etlingera balikpapanensis for potential biofertilizer development and conservation strategies - ALMANDO GERALDI; FATIMAH FATIMAH; RICO RAMADHAN; NI’MATUZAHROH NI’MATUZAHROH; HERY SUWITO; NABILLA HAPSARI WIJAYA; YANA ZAINADA VIRDAUS; RICA HANIM FADHILAH; ARRIZAL RAHMAN; LUKMAN RIYADI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Geraldi A, Fatimah, Ramadhan R, Ni’matuzahroh, Suwito H, Wijaya NH, Virdaus YZ, Fadhilah RH, Rahman A, Riyadi L. 2025. Exploring the bacteriome of Etlingera balikpapanensis for potential biofertilizer development and conservation strategies. Biodiversitas 26: 2548-2555. Etlingera balikpapanensis, an endangered and endemic plant species from the rainforests of East Kalimantan, Indonesia, faces significant threats due to habitat loss and environmental changes. Conservation strategies for this species are limited, and there is an urgent need for innovative approaches to enhance its survival, particularly in ex-situ environments. One promising avenue is the development of biofertilizers derived from beneficial microbial communities. These Plant Growth-Promoting Bacteria (PGPB), which exist in both endophytic and rhizospheric environments, can improve nutrient uptake, enhance stress tolerance, and protect against pathogens. We used high-throughput 16S rRNA gene sequencing to characterize the endophytic and rhizospheric bacterial communities associated with E. balikpapanensis. We identified 1,183 Operational Taxonomic Units (OTUs) from plant tissues and soil samples. Among these, we found bacterial species known for their plant growth-promoting properties, including Pantoea dispersa and Kluyvera intermedia in plant tissues, as well as Burkholderia pyrrocinia, and Bradyrhizobium elkanii in soil samples. These potential microbes, with their proven plant growth-promoting properties, offer hope for the conservation of E. balikpapanensis. They can be used in biofertilizer formulation that could support the species' survival by improving its resilience to environmental stresses. The identification of such microbial communities offers a foundation for developing sustainable conservation practices that leverage natural symbiotic relationships. Future efforts should focus on isolating and characterizing these bacterial strains for experimental biofertilizer applications, aiming not only to enhance the growth of E. balikpapanensis, but also to aid the conservation of other endangered species within the Zingiberaceae family.